Dynamical Behavior of an eco-epidemiological Model involving Disease in predator and stage structure in prey - Ahmed, Lina Shihab; AL- Husseiny, Hassan Fadhil (Iraqi Journal of Science, 2019)
An eco-epidemic model is proposed in this paper. It is assumed that there is a stage structure in prey and disease in predator. Existence, uniqueness and bounded-ness of the solution for the system are studied. The existence of each possible steady state points is discussed. The local condition for stability near each steady state point is investigated. Finally, global dynamics of the proposed model is studied numerically.